2015
DOI: 10.1007/s00705-015-2660-3
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid residues at positions 222 and 227 of the hemagglutinin together with the neuraminidase determine binding of H5 avian influenza viruses to sialyl Lewis X

Abstract: Influenza viruses isolated from ducks are rarely able to infect chickens; it is therefore postulated that these viruses need to adapt in some way to be able to transmit to chickens in nature. Previous studies revealed that sialyl Lewis X (3′SLeX), which is fucosylated α2,3 sialoside was predominantly detected on the epithelial cells of the chicken trachea, whereas this glycan structure is not found in the duck intestinal tract. To clarify the mechanisms of the interspecies transmission of influenza viruses bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 42 publications
4
44
0
Order By: Relevance
“…Our isolates have the amino acid sequence QQG at positions 226–228, which are located at the receptor-binding site in the HA protein, although the corresponding amino acid sequences of the previous H5 viruses are QSG or QRG (Technical Appendix Figure 2). These findings suggest that the receptor specificity of our H5N6 HPAIV isolates might be altered from their parental viruses ( 12 , 13 ). We also found 11 aa deletions in the stalk region of the NA protein, unlike that of A/duck/Vietnam/HU1–1151/2014 (H5N6), a representative virus strain of an N6 NA gene-based group D (Technical Appendix Figure 3), which belongs to a different cluster of the clade 2.3.4.4.…”
Section: The Studymentioning
confidence: 86%
“…Our isolates have the amino acid sequence QQG at positions 226–228, which are located at the receptor-binding site in the HA protein, although the corresponding amino acid sequences of the previous H5 viruses are QSG or QRG (Technical Appendix Figure 2). These findings suggest that the receptor specificity of our H5N6 HPAIV isolates might be altered from their parental viruses ( 12 , 13 ). We also found 11 aa deletions in the stalk region of the NA protein, unlike that of A/duck/Vietnam/HU1–1151/2014 (H5N6), a representative virus strain of an N6 NA gene-based group D (Technical Appendix Figure 3), which belongs to a different cluster of the clade 2.3.4.4.…”
Section: The Studymentioning
confidence: 86%
“…However, the viruses replicated effectively in all three hosts and no statistically significant difference was seen when the maximum viral titres in swabs from each host were compared. The amino acids at positions 222 and 227 are involved in receptor‐binding preferences in avian species (Hiono et al., , ). Some H5 HPAIVs possessing R/Q and R at positions 222 and 227 respectively, in HA bind to fucosylated α2,3 sialoside in their hosts, which is expressed on the epithelial cells of chicken trachea but is not found in the duck intestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…One previous study's findings indicated that recent H5Nx viruses exhibited alterations in their receptor binding specificity compared with previous HPAIVs , these viruses preferring fucosylated α2,3 sialosides in addition to typical non‐fucosylated α2,3 sialosides. Fucosylation of α2,3 sialosides is thought to be a molecular determinant of host preferences by avian influenza viruses in ducks and chickens in that chicken viruses prefer fucosylated α2,3 sialosides whereas duck viruses prefer non‐fucosylated α2,3 sialosides . All the viruses isolated in the present study possess a glutamine at position 222 of the HA, which is a key amino acid residue for the recognition of fucosylated α2,3 sialosides.…”
Section: Discussionmentioning
confidence: 99%